2015
DOI: 10.1177/1742715015590468
|View full text |Cite
|
Sign up to set email alerts
|

Think transformational leadership – Think female?

Abstract: This study examines whether the behaviors of transformational, transactional, and laissez-faire leadership are perceived as being more typical of female or male leaders. In a questionnaire study, 113 participants in Germany were asked to rate the probability of occurrence of a specific leadership behavior for male and female leaders, respectively. A diagnostic ratio for each leadership behavior allows the determination of the direction and degree of gender-specific evaluations. As predicted, transformational l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 55 publications
2
29
1
Order By: Relevance
“…There was no significant difference in the expectation of autocratic leadership behaviours, between female (M = 4.72; SE = .19) and male leaders (M = 4.57; SE = .17), F(1, 44) = .49, p = .487, η 2 p ¼ :01. In line with earlier research (Stempel, Rigotti, & Mohr, 2015), these results suggest that evaluators hold differential expectations about transformational leadership depending on the leader's gender. The finding for autocratic leadership is surprising, because in the past agentic behaviours were found to be expected more of men than women (Diekman & Eagly, 2000).…”
Section: Pretestsupporting
confidence: 79%
“…There was no significant difference in the expectation of autocratic leadership behaviours, between female (M = 4.72; SE = .19) and male leaders (M = 4.57; SE = .17), F(1, 44) = .49, p = .487, η 2 p ¼ :01. In line with earlier research (Stempel, Rigotti, & Mohr, 2015), these results suggest that evaluators hold differential expectations about transformational leadership depending on the leader's gender. The finding for autocratic leadership is surprising, because in the past agentic behaviours were found to be expected more of men than women (Diekman & Eagly, 2000).…”
Section: Pretestsupporting
confidence: 79%
“…In this study, the female NMs reported higher level of Management-By-Exception (Passive). However, previous studies [58,59] confirmed that female groups tend to show TL styles more often. The discrepancy may perhaps be attributed to the over-representation of female gender (86%) in a small sample (n = 78) in this study.…”
Section: Management-by-exceptionmentioning
confidence: 87%
“…Women's leadership often focuses on the distinctiveness of female leaders, women's proclivities for particular styles of leadership such as more participation-orientated approaches, or how gender is not a factor in leadership 'effectiveness' at all (Stempel et al 2015). For others, there is novelty value in seeing women in leadership positions, especially in visible spaces such as politics.…”
Section: A Different Leader? Prime Minister Jacinda Ardernmentioning
confidence: 99%